PENGEMBANGAN MODUL INQUIRY TERBIMBING BERMUATAN NILAI/KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN SIKAP PESERTA DIDIK PADA MATERI JAMUR KELAS XI - Indah Wigati (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to produce a product that is a guided Inquiry module that contains values / characters. This research is a development research developed by Borg & Gall. Data analysis techniques using N-gain score, independent t test and MANOVA test. Product development validation is carried out by material experts, educational media value / character experts. The subjects of this study were students of class X MA Al-Fattah Palembang. Research instruments include modules that are integrated in values / characters, in which there are critical thinking questions and values / characters. Measurement of aspects of critical thinking according to Fascione and attitude based on an integrated questionnaire values / characters according to Einstein consisting of five values / characters namely religious, educational, socio-political, intellectual and practical values. The results of the product research are in the form of modules according to experts